Indian History and Culture in the Volgograd Oriental Studies - Vasiliy V. Tarakanov; Irina K. Cheremushnikova; Aleksandr A. Kiselev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2017)
The article is devoted to the study of Indian history and culture in Volgograd in the late 20th – early 21th century under the guidance of famous Russian orientalists Arkady Ya. Serebryany and Evgeny L. Besprozvannyh. The authors write about their organizational, scientific and pedagogical activity. Scientific works of Volgograd orientalists, who are pupils of Arkady Ya. Serebryany and Evgeny L. Besprozvannyh, are noted.